Design of PI controller using MRAC techniques for coupled-tanks process - Kangwanrat, Suparoek; Tipsuwannaporn, Vittaya; Numsomran, Arjin (My University, 2010)
The typical coupled-tanks process that is TITO plant has the difficulty in controller design because changing of system dynamics and interacting of process. This paper presents design methodology of auto-adjustable PI controller using MRAC technique. The proposed method can adjust the controller parameters in response to changes in plant and disturbance real time by referring to the reference model that specifies properties of the desired control system. ©ICROS.
Keywords: Coupled-Tanks process; MRAC; PI controller